Conformational changes in the essential E. coli septal cell wall synthesis complex suggest an activation mechanism - Britton, Brooke M. (2023)
Funding Information: The authors thank all members of the Hensel, Xiao, and Lau laboratories for helpful discussions and feedback on the manuscript. Z.H. received support for this work from FCT—Fundação para a Ciência e a Tecnologia, I.P., through MOSTMICRO-ITQB R&D Unit (UIDB/04612/2020, UIDP/04612/2020, Z.H.) and LS4FUTURE Associated Laboratory (LA/P/0087/2020, Z.H.), from a joint research agreement with the Okinawa Institute of Science and Technology, and from the Google Cloud Research Credits program with the award GCP20210916. S.F.C. received support from FCT Fundação para a Ciência e a Tecnologia, I.P., through a PhD fellowship (PD/BD/135480/2018, SMC). Work in the Xiao laboratory was supported by NIH F32GM143895 (B.M.B.), NIH T32GM007445 (J.W.M), and R35GM136436 (J.X.). Work in the Lau laboratory was funded by the Johns Hopkins Catalyst Award (to A.Y.L.); NIH T32GM135131 (to R.A.Y.). Anton 2 computer time (MCB130045P) was provided by the Pittsburgh Supercomputing Center (PSC) through NIH grant R01GM116961 (to A.Y.L.); the Anton 2 machine at PSC was generously made available by D.E. Shaw Research. We also used resources provided by Advanced Research Computing at Hopkins (ARCH) at Johns Hopkins University. Funding Information: The authors thank all members of the Hensel, Xiao, and Lau laboratories for helpful discussions and feedback on the manuscript. Z.H. received support for this work from FCT—Fundação para a Ciência e a Tecnologia, I.P., through MOSTMICRO-ITQB R&D Unit (UIDB/04612/2020, UIDP/04612/2020, Z.H.) and LS4FUTURE Associated Laboratory (LA/P/0087/2020, Z.H.), from a joint research agreement with the Okinawa Institute of Science and Technology, and from the Google Cloud Research Credits program with the award GCP20210916. S.F.C. received support from FCT Fundação para a Ciência e a Tecnologia, I.P., through a PhD fellowship (PD/BD/135480/2018, SMC). Work in the Xiao laboratory was supported by NIH F32GM143895 (B.M.B.), NIH T32GM007445 (J.W.M), and R35GM136436 (J.X.). Work in the Lau laboratory was funded by the Johns Hopkins Catalyst Award (to A.Y.L.); NIH T32GM135131 (to R.A.Y.). Anton 2 computer time (MCB130045P) was provided by the Pittsburgh Supercomputing Center (PSC) through NIH grant R01GM116961 (to A.Y.L.); the Anton 2 machine at PSC was generously made available by D.E. Shaw Research. We also used resources provided by Advanced Research Computing at Hopkins (ARCH) at Johns Hopkins University. Publisher Copyright: © 2023, The Author(s).